Formulation Design and Evaluation of Hydrogel-Based Metronidazole Bioadhesive Tablet for Vaginal Candidiasis: Hydrogel based tablet for vaginal candidiasis - Umme Hani; H.G. Shivakumar; Gowrav MP (Iranian Journal of Pharmaceutical Sciences, 2024)
Hydrogel-Based Metronidazole Bioadhesive Tablet (HMBT) was prepared as a novel vaginal delivery system to achieve Controlled release of drug from the tablet for vaginal candidiasis. The highly swollen hydrogel were prepared by dissolving chitosan in acetic acid solution containing drug, followed by neutralisation with sodium hydroxide and characterized by SEM, DSC and FT-IR and evaluated for % swelling. The drug loaded hydrogels were incorporated into tablet formulation by dry granulation method using bioadhesive polymers such as HPMC, sodium CMC and guar gum in different ratios. HMBT was tested for drug content, hardness, friability, weight variation, thickness, swelling studies, in vitro drug release, bioadhesive strength, in vivo studies and antifungal activity. The FT-IR and DSC spectra’s revealed that there was no chemical interaction between drug and polymers used. SEM revealed that particles of hydrogels appeared small and irregular shaped with large numbers of pores. F3 formulation shows good in vitro release profile with highest bioadhesive strength. From the in vivo study in rabbit it was found that the HMBT hold the tablet for more than 12 hours inside the vaginal tube. It may be concluded from present study that HMBT can be used as a novel delivery system for local therapy of vaginal candidiasis which can controlled the release of drug for prolong period of time.